(untitled) (Revista de Ciências Agroveterinárias, 2015)
The objective was to evaluate behavioral characteristics of mares in estrus and diestrus period that were subjected to techniques of artificial insemination and embryo transfer, in an equine reproductive clinic. 16 Mangalarga Marchador, Quarter Horse, and Campolina, aged between 3 and 12 years, and weighing between 490 and 740 kg were used. They were housed in individual stalls 4 x 4 meters in size, having access to a paddock for a few hours of exercise each day. The mares were observed for a period of 24 hours, noting every ten minutes the activities and the time spent by each animal in these activities, at the stages of estrus and diestrus, analyzing the behavioral parameters: frequency of urination, frequency of defecation, resting time, time spent feeding, frequency of water consumption, walking time, time sleeping standing up, time sleeping lying down, time sleeping in total decubitus, and deviations from the norm. There was no difference between the external behavior mares during different periods, differing (P<0.05) only for frequency of urination and time sleeping lying down, which were higher in mares in estrus. Thus, mares in estrus urinate more frequently and, due to higher daytime anxiety, need more time to rest.